Photocatalytic activity of hydrothermally synthesized Al2O3graphene nanocomposite - Mohamad Isa, Nur Farihah; Nik Yusoff, Nik Raihan; Razali, Mohd Hasmizam; Yusoff, Mahani (SCOPUS, 2018)
In this study, Al2O3-graphene nanoplatelets (GNP) nanocomposite was evaluated on its properties and performance towards methyl orange (MO) dye. Al2O3-GNP nanocomposite was prepared by conventional hydrothermal at 200°C for 24 h. The result showed the crystallite size of Al2O3 is decreased and internal strain increased with the increased GNP content. The particle size of nanocomposite becomes larger with the increment GNP amount in the nanocomposite. Nanocomposite with lower graphene contents (20 wt%) and higher Al2O3 contents performed (80 wt%) the optimum for the MO absorption with efficiency of 75% in visible light.